An Analysis of Indonesia’s Foreign Policy in Handling The North Natuna Sea Conflict in 2017-2022 - Abdul Latief (Mediasi Journal of International Relations, 2023)
China claims 90% of the area in the South China Sea, including the North Natuna Sea which is owned by Indonesia. As an area that borders other countries and is involved in an ownership dispute with China, violations of sovereignty are prone to occur in this area. In 2016, Chinese fishing boats often committed illegal fishing in the North Natuna Sea. At the peak, KRI Imam Bonjol shot the Han Than Chou ship that was caught spreading nets in Natuna waters. This invited protests from China which were responded to by President Joko Widodo's visit to Natuna and held a meeting to discuss the acceleration of Natuna's development on KRI Imam Bonjol with the ranks of ministers and the TNI Commander and Chief of Police. This research uses qualitative method, to process data from books, journals, articles, scientific papers, and newspapers. From this research, it is found that at least 3 foreign policy measures were adopted by Indonesia to maintain state sovereignty. This step consists of changing the name of the South China Sea region to the North Natuna Sea in a map published in 2017. Then, to strengthen state sovereignty in the North Natuna Sea, the Government mobilized hundreds of North Coast fishermen to go to sea in the Natuna Sea. To enhance the two policies taken, President Joko Widodo issued Presidential Regulation No. 41 of 2022 concerning zoning plans for inter-regional areas in the North Natuna Sea. The emergence of this Perpres is expected to accelerate development programs to strengthen the country's resilience, grow the economy, and preserve nature in Natuna.